Implementation of Pulmonary TB Case Finding on the Tuberculosis Control Program at the Karangmalang Primary Healthcare Center Semarang City - Ulfa, Siti Lutfiyah; Saefurrohim, Muhamad Zakki (Mulawarman International Conference on Tropical Public Health, 2025)
CDR of Tuberculosis at Karangmalang Primary Health Care from 2016 to 2018 was has always been the lowest in Semarang City. The low CDR can be interpreted by the low performance of the implementers in implementation Pulmonary TB case discovery at Karangmalang PHC. This research aimed to knew the implementation of Pulmonary TB case discovery at Karangmalang PHC. Methods: This research used qualitative design with research type is case study. The informants were selected by purposive sampling were consisted of 5 main informants and 4 triangulation informants. Data were collected using in-depth interviews and then the data were analyzed and presented in narrative form.Results: The results showed that standards and targets of policy were clear, resource readiness was good, the quantity of TB cadres was lacking, communication and coordination between organizations was good, the dissemination of information related to tuberculosis to the community was lacking, there was no SOP for Pulmonary TB case detection, the understanding and performance of the implementers was still lacking, and community participation needs to be increased.